IMPLEMENTASI SISTEM PENGAJUAN CUTI KARYAWAN BERBASIS WEB DENGAN METODE EXTREME PROGRAMMING: STUDI KASUS PT DELTA TEKNO PERKASA - Abdurrobi Elman Sudri; Sopiyan Apandi (LPPM Politeknik Pratama Kendal, 2025)
This study addresses the challenges of manual leave management at PT Delta Tekno Perkasa, which cause administrative errors, inefficient workflows, data inconsistency, and a lack of transparency. To solve these issues, the research focuses on developing a web-based employee leave application system.The system is developed using the Extreme Programming (XP) methodology, an Agile model prioritizing flexibility, frequent iterations, and continuous user involvement. The design incorporates multiple user roles—employees, supervisors, managers, and HR—each with defined access and workflow responsibilities to ensure secure and structured processing.The anticipated result is a responsive and reliable web application that automates the entire request and approval cycle. Implementation aims to significantly reduce administrative workload, improve record accuracy, and enhance organizational transparency and accountability. Ultimately, the system is expected to serve as a foundational platform for future HRIS development within the company.